1992
DOI: 10.1007/bf02245479
|View full text |Cite
|
Sign up to set email alerts
|

Motor activity following the administration of selective D-1 and D-2 dopaminergic drugs to MPTP-treated common marmosets

Abstract: Abstract.The ability of selective D-1 agonist and antagonist drugs to alter motor deficits and locomotor activity was studied in MPTP-treated common marmosets. Both the D-2 agonist quinpirole and the mixed D-l/D-2 agonist apomorphine reversed the motor impairments and induced locomotor activity. The D-I antagonist SCH 23390 and the D-2 antagonist raclopride given alone further reduced motor function in MPTP-treated animals. The actions of quinpirote were potently and completely inhibited by raclopride but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Locomotor and behavioural deficits were induced by subcutaneous administration of MPTP (1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine hydrochloride; Research Biochemical International, Natick, MA) 2.0 mg/kg daily for 5 consecutive days dissolved in sterile 0.9% saline solution 34, 35. Over the following 6 to 8 weeks, animals were hand fed on a daily basis with Mazuri marmoset jelly until the animals had recovered from the acute motor effects of MPTP treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Locomotor and behavioural deficits were induced by subcutaneous administration of MPTP (1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine hydrochloride; Research Biochemical International, Natick, MA) 2.0 mg/kg daily for 5 consecutive days dissolved in sterile 0.9% saline solution 34, 35. Over the following 6 to 8 weeks, animals were hand fed on a daily basis with Mazuri marmoset jelly until the animals had recovered from the acute motor effects of MPTP treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Interruptions of an infrared beam, by movement were automatically recorded as a single locomotor count. Locomotor counts were accumulated over 30‐minute periods for the 8‐hour duration of experimentation 35. Throughout the study, animals had ad libitum access to Mazuri marmoset food pellets and fresh water.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline motility counts were measured approximately 2 weeks before administration of piribedil or L ‐dopa, and animals were subsequently allocated to treatment groups such that basal motility counts in each group was equivalent. The monitor was started immediately after drug administration and motility counts were accumulated over 30‐minute periods for 8 hours 13, 64, 65…”
Section: Methodsmentioning
confidence: 99%
“…Behavior was rated qualitatively to determine the presence or absence of grooming, stereotyped activity, retching/vomiting, oral movements, or other unusual motor activities. Assessments were undertaken by skilled behavioural pharmacologists (not blinded to drug treatments) with many years of experience in this field 13, 45–47, 64–67…”
Section: Methodsmentioning
confidence: 99%
“…The MPTP-treated common marmoset exhibits stable parkinsonian deÞcits which are reversed by administration of L-dopa and other D 1 /D 2 agents, and by selective D 2 and D 1 -acting compounds (Jenner et al 1984;Temlett et al 1989;Kebabian et al 1992;Löschmann et al 1992). Recently, we have shown that the common marmoset, in common with other MPTPlesioned primate species, develops dyskinesias after chronic L-dopa administration and that repeated administration of the selective D 1 agonist A-77636 to L-dopa-primed MPTP-lesioned marmosets resulted in a gradual reduction in the intensity of dyskinesia with a retained antiparkinsonian e¤ect (Pearce et al 1995).…”
Section: Introductionmentioning
confidence: 98%